Bench-stable transfer reagent facilitates the generation of trifluoromethyl-sulfonimidamides - Wright, M; Martínez-Lamenca, C; Leenaerts, J; Brennan, P; Trabanco, A; Oehlrich, D (American Chemical Society, 2018)
Sulfonimidamides are an emerging bioisosteric replacement in medicinal chemistry projects, and therefore new chemistries are necessary to access this functionality. The general synthesis of CF3-sulfonimidamides from an activated bench-stable transfer reagent is described. A diverse reaction scope is demonstrated, with a wide range of nucleophilic amines being tolerated in this transformation. The CF3-sulfonimidamides obtained contain an additional diversity point, in the form a protected imine, that could be unmasked to allow late stage modifications.